Analysis of the Role of Basketball in Improving Physical Fitness Levels - I Putu Agus Dharma Hita (International Journal of Educatio Elementaria and Psychologia, 2024)
This research aims to delve into the role of basketball in improving physical fitness through a literature review method. Literature analysis was conducted to investigate the impact of basketball's physical activity on aspects of physical health, cardiovascular health, as well as social and psychological aspects of players. Findings from scientific literature indicate that basketball contributes positively to the comprehensive development of strength, speed, and agility. Moreover, the intensity of the game has proven to influence increased heart rate and lung capacity, supporting optimal cardiovascular health. Social and psychological aspects also became a focal point, revealing that team interaction, game strategies, and collective responsibility can enrich players' experiences and potentially enhance their psychological well-being. Meanwhile, the integration of technology in basketball training offers innovative and effective methods to enhance training effectiveness and optimize skill development. The conclusion of this research indicates that basketball is not just a sport but a holistic means to improve physical fitness and overall well-being. As a recommendation, it is suggested that educational institutions and communities consider integrating basketball into their fitness programs and enhance the use of technology to support effectiveness. These conclusions and recommendations are expected to serve as a foundation for the development of more relevant and results-oriented fitness programs.